Role of genetic background in cardiovascular risk markers changes in water polo players - Di Mauro, D.; Curro, M.; Trimarchi, F.; Vecchio, M.; Rizzo, G.; Barreca, D.; Visalli, G.; Ientile, R.; Caccamo, D. (International Journal of Sports Medicine, 2018)
Methylene-tetrahydrofolate reductase (MTHFR) and paraoxonase 1 (PON1) gene polymorphisms have been associated with hyperhomocysteinemia and oxidative stress increase, that are established cardiovascular risk factors. Given that intense physical activity may increase the susceptibility to adverse cardiovascular outcomes, here we investigated the effects of MTHFR C677T and A1298C as well as PON1 Q192R gene polymorphisms on cardiovascular risk markers in twenty-eight male water polo elite players. The mean plasma levels of homocysteine (Hcy) and advanced oxidation protein products (AOPP) were above reference limits in resting conditions, and increased after competition. Moreover, a positive correlation was found between Hcy and AOPP concentrations, and also between their variations (ratio post-exercise/pre-exercise values) and the variations of lactic dehydrogenase (LDH) and creatine kinase (CK) activities, known as muscle damage markers. The highest Hcy and AOPP values were found in subjects having either MTHFR CT/AC or TT/AA, and PON1 QR192 genotype, respectively. After exercise, Hcy concentrations significantly increased in CT/AC or TT/AA subjects than in athletes having other MTHFR genotypes. A training-induced increase in plasma levels of LDH and CK activities, as well as myoglobin concentrations, was also observed, even if significant differences were found only for CK activity in athletes with MTHFR CT/AC or TT/AA athletes.